2016 Joint IEEE International Conference on Development and Learning and Epigenetic Robotics (ICDL-EpiRob) 2016
DOI: 10.1109/devlrn.2016.7846835
|View full text |Cite
|
Sign up to set email alerts
|

Vocal interactions at the dawn of communication: The emergence of mutuality and complementarity in mother-infant interaction

Abstract: Continuous interaction of mother and infant in the first weeks and months of an infant's life entrains the infant on many crucial aspects of how to do things together. Contingencies of gaze, vocalizations, and other movements are slowly routinized; this scaffolds directing of attention to each other and the world and gives to such multimodal interactions meaning. It is within these continuous interactions with caregivers that language emerges, starting from the first nonreflexive vocalizations that infants pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 32 publications
3
30
0
Order By: Relevance
“…Another possibility could be that the exaggerated use of the Acknowledgment phase might cause increased verbal behavior on behalf of the mother. In concert with recent work on the development of infants' sensitivity to turn-taking (Gratier et al, 2015 ) and complementary roles in vocalization (Leonardi et al, 2017 ) this could lead to infants not vocalizing to avoid overlap with the mother.…”
Section: Discussionmentioning
confidence: 75%
“…Another possibility could be that the exaggerated use of the Acknowledgment phase might cause increased verbal behavior on behalf of the mother. In concert with recent work on the development of infants' sensitivity to turn-taking (Gratier et al, 2015 ) and complementary roles in vocalization (Leonardi et al, 2017 ) this could lead to infants not vocalizing to avoid overlap with the mother.…”
Section: Discussionmentioning
confidence: 75%
“…Using an earlier established dialogicity of actions (now-you, now-me) parents establish the same pattern in a vocal domain. This process can be observed from the earliest months, first in the emergent turn-taking structure of actions (e.g., Kaye & Wells, 1980) and then in the vocal modality (Leonardi et al, 2016). In the latter case, we observe a decrease in the probability of overlaps between the ages of 3 and 6 months (Figure 4), which stands in contrast to, for example, progressively coupled structure of gaze in the same age range (increase in the probability of mutual gaze, where instead of the valley, present in Figure 4, we observe a peak at the 0 lag; Nomikou et al, 2016).…”
Section: Emergent Linguistic Layermentioning
confidence: 99%
“…Nomikou et al's [24] study considered only gazing behavior (defined as gaze at interaction partner's face), and used CRQA to confirm a tight synchronization of gazing between infants and their mothers and also show how this changes developmentally from the ages of 3, to 6, to 8 months. Similarly, Leonardi et al [48] applied the same method to the vocalization of behavioral streams and found a systematic lagging of mother's vocalizations after infants' vocal production together with an active avoidance of synchronous vocal behavior by the two actors; that is, first signs of vocal turn-taking.…”
Section: Approaches To Multimodal Turn-takingmentioning
confidence: 97%
“…We achieved this by simplifying the behavioral coding in the various modalities to a series of binary codes: presence or absence of a given behavior. Using the same corpus as in [24] and [48], we asked whether gazing behavior could be related to vocalizations; in other words, whether there is a systematic relationship in time between the production of any kind of vocalization in one of the actors and gazing in the other.…”
Section: Approaches To Multimodal Turn-takingmentioning
confidence: 99%
See 1 more Smart Citation